2021
DOI: 10.1107/s2052252521008125
|View full text |Cite
|
Sign up to set email alerts
|

Observation of substrate diffusion and ligand binding in enzyme crystals using high-repetition-rate mix-and-inject serial crystallography

Abstract: Here, we illustrate what happens inside the catalytic cleft of an enzyme when substrate or ligand binds on single-millisecond timescales. The initial phase of the enzymatic cycle is observed with near-atomic resolution using the most advanced X-ray source currently available: the European XFEL (EuXFEL). The high repetition rate of the EuXFEL combined with our mix-and-inject technology enables the initial phase of ceftriaxone binding to the Mycobacterium tuberculosis β-lactamase to be followed using time-resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 76 publications
3
75
0
1
Order By: Relevance
“…As research interest moves away from just photoactive proteins, demand for alternative triggering methods increases. However, if the research target is simultaneously light-unresponsive and mechanistically fast, methods such as rapid mixing (ms) [32,70,71] and even temperature jumps (ns) [68] become too slow, with light triggering methods remaining at the fastest timescales (up to fs bond breaking timescale [72]). A promising method to artificially implement light sensitivity is the use of photocages.…”
Section: Tr-sfx With Light-unresponsive Biomacromoleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…As research interest moves away from just photoactive proteins, demand for alternative triggering methods increases. However, if the research target is simultaneously light-unresponsive and mechanistically fast, methods such as rapid mixing (ms) [32,70,71] and even temperature jumps (ns) [68] become too slow, with light triggering methods remaining at the fastest timescales (up to fs bond breaking timescale [72]). A promising method to artificially implement light sensitivity is the use of photocages.…”
Section: Tr-sfx With Light-unresponsive Biomacromoleculesmentioning
confidence: 99%
“…Time-resolved serial femtosecond crystallography (TR-SFX) is defined by the study of biomacromolecular reactions observed with time resolutions as rapid as femtosecond-scale using SFX [15,21,22]. Since the first published TR-SFX experiment in 2012 at LCLS [23], many studies have been reported [24][25][26][27][28][29][30][31], including those conducted at the European XFEL that made use of its ultra-fast repetition rate [18,32,33]. As time-resolved studies require much more data to be collected in comparison to regular SFX (N times more, where N is the number of desired time points to obtain reliable difference electron density maps), the megahertz repetition rate represents a significant advantage in data collection time [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is very important to understand the molecular action to time-resolve the structural change by adding a substrate or inhibitor to the crystal sample. Recently, time-resolution studies for hydratase [69], cytochrome c oxidase [70], and β-lactamase [71] using a solution pump application have been reported. These remarkable advances in time-resolved SX research could be used as a very useful tool to further understand life phenomena.…”
mentioning
confidence: 99%
“…In a second example, the role of a conformational change within the chloride channel was elegantly used to explain the pumping mechanism across the membrane (Yun et al 2021). However, most biological systems are not light-sensitive, so a rapid mix and inject strategy needs to be employed (Pandey et al 2021). The elegant movies which result readily allow for visualizing changes occurring to both substrate and enzyme during catalysis.…”
mentioning
confidence: 99%